Foreign Body Removal from Left Atrium following Successful PTMC - A Case Report - Ulla, M; Majumder, AAS; Rahman, Z (Cardiovascular Journal, 2010)
With the advent of new technology and hardware. Percutaneous transluminal Mitral Commissurotomy (PTMC) is a safe procedure now-a-days. But it is still a costly procedure for the patients of develops countries like Bangladesh. So, the balloon and hardware is still practiced in some countries. One of the possible but rare complication of reuse in trained cover of the guide wire. We are reporting a case of retained cover of guide wire in LA during PTMC. It was successfully renounced wing a name. Keywords: Foreign body removal; PTMC; Snare DOI: 10.3329/cardio.v3i1.6431 Cardiovasc. j. 2010; 3(1): 85-88